Pengaruh Motivasi, Disiplin Kerja, Dan Kepuasan Kerja Terhadap Kinerja Karyawan Konveksi Maudiza Group Malang - Nafisa Nur Aini; Abd Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT The aims of atudy are to portray the motivation, work discipline, job satisfaction and employee performance of the Maudiza Group Convection and to determine the simultaneous and partial influence of motivation, work discipline and job satisfaction on the performance of the Maudiza Group Convection Employee. The sample of this study were all employees, amounting to 40 respondents. Sampling using saturated sampling that is using all members of the population into the sample. The data collection method in this study used a questionnaire and documentation. Data analysis methods used in this study are descriptive and multiple regression analysis. The results of this study indicate that (1) motivation, work discipline and job satisfaction simultaneously have a significant effect on employee performance, (2) motivation has a positive and significant effect on employee performance, (3) work discipline has a negative and significant effect on employee performance, (4) job satisfaction has a positive and significant effect on employee performance. Keywords: Motivation, Work Discipline, Job Satisfaction And Employee Performance.